Shifting orientation in Sufism: its development and doctrine adjustment in history - elmansyah al-haramain (IAIN Salatiga, 2011)
One of Islamic cultures that is constantly able to evolve and adapt to the variouscondition is Sufism. In the process of development, Sufism has always been asolution to various issues in society, and it is also aimed at achieving closedrelation to the Lord. Shifting orientation of Sufism has occurred in any kind of itstheology, politics, philosophy, and organization. The present studies of Sufismdevelopment lead to medical issues. Some experts call it Sufi Healing. It isinteresting to discuss it since the shifting orientation brings something positive tothe development of Sufism. However, there are many things that need to bereviewed, namely the provision of the proposition for any behavioral recoverywhich seemed a merely justification. This article is presented by using ahistorical and a phenomenological approach that emphasizes on the existenceof its phenomenon. Through this article, it is expected to obtain an understandingof Sufism and its various efforts in developing the doctrine of al-ihs an in Islam inhe context of digital era.Salah satu hasil kebudayaan Islam yang senantiasa mampu berkembang danberadaptasi secara kondisional adalah tasawuf. Dalam proses perkembangannyaitu, tasawuf selalu menjadi solusi bagi pelbagai persoalan masyarakat, dan mengarahkannya pada kedekatan diri dengan Tuhan. Pergeseran orientasi terjadidi setiap perubahan bentuk, mulai dari teologis, politis, filosofis, organisatoris.Studi tentang perkembangan tasawuf akhir-akhir ini, mulai mengarah padapersoalan medis. Para ahli menyebutnya Sufi Healing. Hal ini menarik untukdibahas, karena pergeseran orientasi ini membawa hal positif bagi perkembangantasawuf. Akan tetapi, ada hal yang nampaknya perlu dikaji ulang, yakni pemberiandalil atas setiap perilaku penyembuhan, yang seolah-olah merupakan justifikasibelaka. Tulisan ini disajikan dengan menggunakan pendekatan sejarah; Analisisnyamenggunakan pendekatan fenomenologis. Melalui tulisan ini, diharapkan dapatdiperoleh pemahaman tentang tasawuf dan berbagai upayanya dalammengembangkan ajaran al-ihsan dalam Islam dalam konteks era digital.